Assuring high reliability of service provision in critical infrastructures. (3rd April 2006) - De Bruijne, Mark; Van Eeten, Michel; Roe, Emery; Schulman, Paul
Vital services that are provided through critical infrastructures such as electricity and mobile telecommunication present us with a paradoxical development: society demands increasing levels of reliability of these services as we grow more dependent on them, while at the same time the conventional organisational means with which to ensure those high levels of reliability are being dismantled. Developments such as liberalisation, technological innovation and outsourcing have made the provision of highly reliable services through critical infrastructures increasingly the product of networks of organisations, rather than individual or a limited set of organisations. A key question for next generation critical infrastructures is therefore: how can networks of organisations, many with competing goals and interests, provide highly reliable services in the absence of conventional forms of command and control and in the presence of rapidly changing circumstances, technologies and demands? This paper reports on extensive field research that suggests the answer to complexity, and institutional change may be found in real time.